Lost birds - Hillerman, Anne, 1949- (Hillerman, Tony. Leaphorn and Chee novel, 2024)
Joe Leaphorn may be long retired from the Navajo Tribal Police, but his detective skills are still sharp, honed by his work as a private detective. His experience will be essential to solve a compelling new case: finding the birth parents of a woman who was raised by a bilagáana family but believes she is Diné based on one solid clue, an old photograph with a classic Navajo child's blanket. Leaphorn discovers that his client's adoption was questionable, and her adoptive family not what they seem. His quest for answers takes him to an old trading post and leads him to a deadly cache of long-buried family secrets. As that case grows more complicated, Leaphorn receives an unexpected call from a person he met decades earlier. Cecil Bowleg's desperation is clear in his voice, but just as he begins to explain, the call is cut off by an explosion and Cecil disappears. True to his nature, Leaphorn is determined to find the truth even as the situation grows dangerous. Investigation of the explosion falls in part to Officer Bernadette Manuelito, who discovers an unexpected link to Cecil's missing wife. Bernie also is involved in a troubling investigation of her own: an elderly weaver whose prize-winning sheep have been ruthlessly killed by feral dogs.